When the skin speaks: cutaneous vasculitis complicating a Klebsiella urinary tract infection - Shifa, Fathima; Rao K. S., Apurva (International Journal of Advances in Medicine, 2025)
Cutaneous small-vessel vasculitis (CSVV) occurs due to leukocytoclastic vasculitis of dermal post-capillary venules. It can be triggered by infections, autoimmune conditions, or medications. Our case report highlights a rare association between CSVV and a urinary tract infection caused by Klebsiella pneumoniae in an immunocompetent individual. A 31-year-old female with no prior known comorbidities presented with painful, pruritic lesions over both lower limbs and right arm preceded by gastrointestinal symptoms. On examination, there were erythematous macules, crusted plaques and haemorrhagic vesicles noted. A skin biopsy confirmed CSVV. Autoimmune markers were negative, while complement C3 levels were reduced. Urine culture grew Klebsiella pneumoniae, suggesting a post-infectious etiology. The patient was treated with antibiotics and steroids resulting in marked clinical improvement. Infections are common triggers of CSVV, however Klebsiella pneumoniae is an uncommon cause, particularly in immunocompetent individuals. This case underlines the importance of considering uncommon etiologies in the differential diagnosis of CSVV and emphasizes that prompt identification and treatment of the underlying infection can lead to complete resolution. This case contributes to the limited literature on Klebsiella pneumoniae-associated CSVV in immunocompetent individuals and underscores the value of biopsy, infectious work-up, and early therapy in achieving good outcomes.